Living with support: Experiences of people with mild intellectual disability - Giesbers, Sanne A. H. (J Appl Res Intellect Disabil, 2018)
BACKGROUND: To enhance social inclusion of people with intellectual disability, policy is aimed at increasing informal support networks. Nevertheless, staff continue to play a vital role in their support networks. METHOD: Six individuals with mild intellectual disability, living in community‐based settings, were interviewed following a semi‐structured format. In‐depth accounts of participants’ support experiences were established using Interpretative Phenomenological Analysis. RESULTS: Three main themes were identified: relationships with staff placed within a personal history, relationships with staff within an organisational context, and staff support and interviewees’ place in the world. CONCLUSIONS: Relationships with staff were often one of the closest and most significant social relationships participants had. As living in the community had not necessarily led to meaningful inclusion for participants, the findings point at the important role of staff in supporting and facilitating friendships and close relationships of people with intellectual disability.